Rescaling of aerial survey data with information from small numbers of telemetry tags to estimate the size of a declining harbour seal population - Lonergan, Mike; Duck, Callan; Moss, Simon; Morris, Chris; Thompson, Dave (Aquatic Conservation: Marine and Freshwater Ecosystems, 2013)
Estimates of both absolute abundance and trends in abundance are among the most basic pieces of information required for planning the conservation and management of wildlife populations. They are important for understanding both the current situation of species and potential risks to them. This study presents estimates of the size of the harbour seal (Phoca vitulina) population associated with the Orkney Islands, a part of northern Scotland that used to contain one of the largest concentrations of this species in Europe. The numbers of animals counted during aerial surveys of this area have decreased substantially over the period 2001-2010. ARGOS transmitters attached to flipper tags were used to rescale the counts into estimates of abundance and to confirm the rate of decline of this population. Females hauled out for more of the survey window (0.84; bootstrap 95% CI: 0.63-0.99) than males (0.61; bootstrap 95% CI: 0.34-0.86). The animals hauled out less during weekends (0.57; bootstrap 95% CI: 0.40-0.74) than during the week (0.76; bootstrap 95% CI: 0.58-0.91). The sex-ratios of this population is unknown. Assuming it was close to 1:1, then there were around 3586 (bootstrap 95% CI: 2970-4542) harbour seals in Orkney in 2010. A female-skewed sex-ratio would reduce the population estimate, and a changing sex-ratio might mean the counts understate the real decline. The mean annual rate of decline in the Orkney population of harbour seals, over the period 2001-2010, is estimated at 13% (95% CI: 10.8-14.8). Similar data for Arisaig, on the west coast of Scotland, shows an increase of around 2% (95% CI: 1.5-2.4) and, assuming an equal sex-ratio, 923 animals (95% CI: 765-1169) in 2007.